2014
DOI: 10.1177/1038416214535109
|View full text |Cite
|
Sign up to set email alerts
|

Perceived social support as predictors of adolescents’ career exploration

Abstract: The aim of this study was to examine whether adolescents' career exploration is predicted by perceived social support. Participants were 718 seventh, eighth, ninth and tenth grade students. In this research, simultaneous regression analysis assessed the contributions of perceived social support to the adolescent's career exploration. Perceived family social support, perceived friends' social support, and perceived significant other social support correlated significantly with the career exploration. The simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 33 publications
(59 reference statements)
2
20
0
3
Order By: Relevance
“…Friends were cited as the most frequent source of discouraging messages about particular careers, followed by mothers and fathers. This result supports prior research finding perceived social support from friends to be more strongly related to students' career exploration than perceived support from family (Turan et al, 2014). Friends were identified as most frequently discouraging career interests about particular careers by commenting that it would not suit the students' passions or interests, supporting previous research that found friends to be a valuable reality check (Levine & Hoffner, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…Friends were cited as the most frequent source of discouraging messages about particular careers, followed by mothers and fathers. This result supports prior research finding perceived social support from friends to be more strongly related to students' career exploration than perceived support from family (Turan et al, 2014). Friends were identified as most frequently discouraging career interests about particular careers by commenting that it would not suit the students' passions or interests, supporting previous research that found friends to be a valuable reality check (Levine & Hoffner, 2006).…”
Section: Discussionsupporting
confidence: 85%
“…The present study’s findings are consistent with the results of previous research about adolescent–parent career congruence (Dietrich & Kracke, 2009; Nota et al., 2007; Oettingen & Zosuls, 2006; Perry et al., 2010). According to these researchers, adolescent–parent career congruence and parental support, which includes parental expectations, encouragement, instrumental assistance, modeling the desired behaviors, and emotional backing, are the most important variables affecting adolescent career development and career exploration: parental and social support for career development influences career identity evaluation (Stringer & Kerpelman, 2010) and career exploration (E. Turan, Çelik, & Turan, 2014). Thus, adolescent–parent career congruence is a critical issue for parents and their children when it comes to career issues.…”
Section: Discussionmentioning
confidence: 99%
“…It suggests that perceived social support may contribute in one way or the other to the development process of career adaptability skill among young adults, such as, higher education students in Nigeria. In a study conducted in Turkey to examine whether perceived social support predicts career exploration, it was found that family, friends, and significant others correlated significantly with career exploration (Turan et al, 2014). The study also reported that family, friends, and significant others predicted career exploration among young adults in higher education.…”
Section: Perceived Social Supportmentioning
confidence: 98%
“…(ii) Multiple linear regression (MLR) was used for the analysis, although, the use of structural equation modeling (SEM) or path analysis would have given more plausible causality details of the relationship between the predictors and the outcome variable. the choice of MLR for analysis was because the researchers were simply interested in understanding the basic relationship between the predictor variables and the criterion variable of the study (Creed and Fallon, 2009;Yousefi et al, 2013;Turan et al, 2014). For these reasons, the researchers wish to suggest that (i) future studies should be conducted to cover other academic program in the tertiary institutions in Nigeria, and (ii) that future researchers should endeavor to use SEM for analysis of causal relationship between the predictors and the outcome variables for more plausible results.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%